METHODOLOGY FOR RESEARCH ON TRAFFIC SAFETY AT SIGNALIZED INTERSECTIONS WITH COUNTDOWN TIMERS - Aleksander SOBOTA; Grzegorz KAROŃ; Renata ŻOCHOWSKA; Marcin KŁOS (Scientific Journal of Silesian University of Technology. Series Transport)
The article is a presentation of the authors‘ research work on determining the impact of countdown timers on traffic conditions, and - in this case - on the level of traffic safety at intersections. Therefore, the scientific aim of the article is to present the methodology used by the authors to carry out research in order to determine the influence of the function of the intersection with countdown timers within an urban transportation network on the level of safety at the intersection. To achieve the scientific objectives, measurements of traffic at three intersections with different functions in a transportation network have been performed.